Merci Suárez changes gears - Medina, Meg (Candlewick Press, 2020)
Middle schooler Merci Suarez is at Seaward Pines Academy on a scholarship, unlike her mostly rich classmates, and she lives in three tiny houses with her extended family, houses they call affectionately Las Casitas. This year, sixth grade, will bring new challenges to Merci's life, from her rival, the school's queen bee Edna Santos wanting to take Merci's Sunshine Buddy, Michael Clark, from her, to Merci's grandfather Lolo acting differently than his usual self. Things escalate, and finally Merci's family must face the issue they have been avoiding.